LANGUAGE EDUCATION AS AN INTEGRAL COMPONENT OF PERSONAL AND PROFESSIONAL SPECIALIST GROWTH - Shadmanova Nigora Irgashevna (American Journals, 2023)
The article examines the features of language education in a technical university, emphasizes its importance and relevance for a modern specialist. The authors analyze the current state of language teaching in technical universities of Uzbekistan and Russia, highlighting the conditions for its intensive and effective development. Some proposals for the modernization of the existing system of language education at the university, the introduction of innovative technologies in the educational process are presented.
Keywords: language teaching, approaches to the learning process, innovative methods, new technologies.